2016
DOI: 10.1108/jfc-05-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Cash economy: tax evasion amongst SMEs in Malaysia

Abstract: Purpose The purpose of this study is to investigate the relationship between tax evasion and certain demographic factors such as location, engagement of tax agent, size and type of small- and medium-sized enterprises (SMEs) industry in Malaysia. Design/methodology/approach In this study, using proprietary tax audit data from the Inland Revenue Board of Malaysia (IRBM) on the 2011 tax returns of SMEs, the authors run a multiple regression analysis to examine the impact of location, agent, type of industry, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 4 publications
0
30
0
2
Order By: Relevance
“…Although SMEs in some countries enjoy preferential taxes, it is also pointed out that most SMEs are missing out of the benefits of international and global businesses as a result of diverse government policies on taxes. Mohamad, Zakaria, and Hamid () found that high and multiple taxes imposed on SMEs are hindering most businesses from potential growth. It is also revealed that the sky‐high tax and tariff imposed by home country is ranked as sixth on problems faced by SMEs at the time of expansion to international market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although SMEs in some countries enjoy preferential taxes, it is also pointed out that most SMEs are missing out of the benefits of international and global businesses as a result of diverse government policies on taxes. Mohamad, Zakaria, and Hamid () found that high and multiple taxes imposed on SMEs are hindering most businesses from potential growth. It is also revealed that the sky‐high tax and tariff imposed by home country is ranked as sixth on problems faced by SMEs at the time of expansion to international market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tidak berarti ketika ada kecurangan pajak disebabkan oleh perilaku agresif konsultan pajak. Penelitian yang dilakukan di Malaysia membuktikan bahwa kecurangan pajak lebih banyak dilakukan oleh usaha kecil menengah yang berada di pinggiran kota tanpa peranan konsultan pajak (Mohamad, Zakaria, & Hamid, 2016). Shafer, Simmons, & Yip (2016) menjelaskan perlunya konsultan pajak memiliki komitmen profesional yang tinggi untuk mencegah tekanan klien yang menginginkan tindakan penghindaran pajak agresif dengan tujuan meningkatkan keuntungan wajib pajak jangka pendek.…”
Section: Pribadiunclassified
“…Setyorini (2016) state that tax socialization has a very important role to increase the willingness to pay SME taxes. SMEs tends to do the tax evasion if there is no or less tax agent in their business area (Mohamad, Zakaria, & Hamid, 2016).…”
Section: Resultsmentioning
confidence: 99%